GIS USING BY EDUCATIONAL MANAGEMENT (PANGEEA, 2025)
The present paper tries to be an example of interdisciplinary research that combines the Informatics Geographical Systems with the educational field in the attempt to provide to the people involved in this domain a new modern and realiable way of development through a modern approach.
Keywords: GIS; Education; Geodatabase; Attribute Domain; Feature Dataset